THE EFFECT OF SUSTAINABILITY REPORT DISCLOSURE ON FIRM VALUE WITH DIVIDEND POLICY AS A MODERATING VARIABLE - Morieta, Yurinda Eka; Aprillianto, Bayu; Wardhaningrum, Oktaviani Ari (Jurnal Akuntansi Bisnis, 2024)
Background: The rising value of Sri-Kehati Index companies in recent years indicates that there is a change in investor orientation towards green investment. Green investment itself has now become a world and government concern which is realized through several regulations. Therefore, companies are required to disclose the sustainability business that has been carried out.Objective: This study aims to analyze the effect of sustainability report disclosure on firm value with dividend policy as a moderating variable.Research Methods: Multiple linear regression analysis and Moderated Regression Analysis (MRA)Research Results: The result showed that sustainability report disclosure has a negative effect on firm value and dividend policy strengthens the negative effect of sustainability report disclosure on firm value.Authenticity/Novelty of Research: The addition of dividend policy as a moderating variable between the relationship between sustainability report disclosure and firm value.